Time perception: Estimation of duration, effects of nontemporal variables, plasticity and conceptual model - Bagdonas , A. (Psichologija, 1985)
In the present paper some aspects of time perception are reviewed and experimentally investigated. The subjects compared the duration of exposition of tachistoscopically presented letters with standard stimulus duration. Compared were the following durations: 0,01; 0,02; 0,04; 0,08; 0,16; 0,32; 0,64; 1,28; 2,56 s, the standard duration being 0,16 s. Under divided attention conditions (2nd series of experiments) the subjects compared the duration of visual stimuli and responded to the offset of simultaneously presented sound. The relation between the subjective and objective time duration was stated to be rather complex. Within the range of 0,16 – 2,56 s this relation was linear (ts = 0,28tf + 120), while in the range of durations shorter than 0,16 s - nonlinear. The interaction of two different mechanisms for perception of short and long durations has been proposed. The duration threshold for visual modality is about 0,1 s. In the range of durations studied the duration of 0,16 s occurred to be estimated most correctly. The neutral interval seemed to be dynamic. The plasticity of time estimation has been illustrated by the results of investigation on set formation and by the tendency towards decreasing in overestimation of time intervals in the process of habituation to the stimulus. The large sized stimuli are perceived as being longer than the small-sized ones. The auditory modality is dominant in the estimation of duration. The increment of number of elements in the test object resulted in shortening the subjective duration. The time of reaction to the offset of sound became longer in case the number of elements in the simultaneously presented test object was increased. The model of polymorphous subjective time continuum has been specified. This polymorphous continuum is composed of six subcontinuums functioning differently: the subthreshold and threshold area durations, the perceptual, the operative memory, and the abstract time, and the orientation in time.